2019
DOI: 10.1007/s00125-019-4955-5
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin and fracture risk in individuals with type 2 diabetes: results from the CANVAS Program

Abstract: Aims/hypothesis An increased risk of fracture with canagliflozin vs placebo was reported from the CANagliflozin cardioVascular Assessment Study (CANVAS) Program, with heterogeneity of findings identified between the two trials that comprise the CANVAS Program, CANVAS and CANVAS-R. The objective of these analyses was to identify reasons for the possibly different effects on fracture observed between CANVAS and CANVAS-R. Methods This study was an analysis of two highly si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 25 publications
1
53
2
6
Order By: Relevance
“…Our results are consistent with those of previous meta-analyses 30,31 in that we find that SGLT2i may have a beneficial effect on fracture in a follow-up of less than 52 weeks, but when this period is extended to more than 52 weeks, this benefit disappears. However, we also found that canagliflozin may increase the incidence of fracture, which is different from the findings of the previous study; this is likely to be because we included the CANVAS study using the newest follow-up data, 17,18 which showed an obvious increase in fracture. Because the CANVAS study introduces heterogeneity to the subgroup analysis of canagliflozin, the heterogeneity drops from 32% to 0 if the CANVAS study is excluded.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with those of previous meta-analyses 30,31 in that we find that SGLT2i may have a beneficial effect on fracture in a follow-up of less than 52 weeks, but when this period is extended to more than 52 weeks, this benefit disappears. However, we also found that canagliflozin may increase the incidence of fracture, which is different from the findings of the previous study; this is likely to be because we included the CANVAS study using the newest follow-up data, 17,18 which showed an obvious increase in fracture. Because the CANVAS study introduces heterogeneity to the subgroup analysis of canagliflozin, the heterogeneity drops from 32% to 0 if the CANVAS study is excluded.…”
Section: Discussioncontrasting
confidence: 99%
“…17 A subsequent study attempted to determine the reasons for this increase in fracture risk, but did not succeed. 18 A study with a follow-up period of 104 weeks found that SGLT2i may be related to an elevated incidence of fracture (7.7% versus 0%). 19 Another study indicated that the decrease in BMD in the canagliflozin group appears to be associated with increased fracture risk, 20 while other studies found that SGLT2is could lower the incidence of fracture.…”
Section: Introductionmentioning
confidence: 99%
“…There was instead no difference in the incidence of fracture in the CANVAS-R study in the canaglifozin vs. placebo group, nor in the most recent CREDENCE trial (104,105). Finally, the analysis of data from the CANVAS and the CANVAS-R trials comprising 10,142 participants concluded that data from the CANVAS trial could be related to chance or presumably to the presence of falls, whose prevalence was not specifically recorded in all studies (106).…”
Section: Sodium-glucose Cotransporter-2 Inhibitorsmentioning
confidence: 92%
“…In the recently published large RCT (CREDENCE study) with canagliflozin, however, no sign of an increased risk for fractures was found [93]. The careful elaboration of the CANVAS and CANVAS-R data showed a significant heterogeneity of the fracture risk in both studies: in the CANVAS study (n = 4330: HR 1.55; 95 % CI 1.21-1.97) the risk was significantly increased, whereas this could not be proven in the CANVAS-R study (n = 5812: HR 0.86; 95 % CI 0.62-1.19) [102].…”
Section: Sglt-2 Inhibitorsmentioning
confidence: 94%